Advances in research in jamun (Syzygium cuminii): a review (Current Horticulture, 2024)
Jamun (Syzygium cuminii Skeels) is an indigenous nutritious medicinal fruit; every part of the tree is utilized by both urban and rural dwellers. The fruit is good source of iron, sugars, minerals, protein, carbohydrate etc. Fully ripe fruits are eaten fresh and can be processed into beverages like jelly, jam, squash, wine, vinegar and pickles.  Fruits and powdered seeds are used as an effective medicine against diabetes. It is an underutilized fruit with a wide range of adaptation to varied edapho-climatic conditions. For better utilization and improvement of its genetic resources, there is a need to understand various aspects. Therefore, basic biology, genetic diversity and varietal wealth, systematic phenology, production technologies, propagation, canopy architecture, biotic and abiotic stress management and value-addition have been discussed.
Keywords: Jamun; Phenology; Genetic diversity; Underutilized fruits; Canopy architecture